Revision of National Standard for Water Chiller and Application of IPLV - 张明圣 (Zhileng xuebao)
This article supports the positive views by analyzing the postive and negative sides of adopting integrated part-load value(IPLV) in the national standard.And it also brings forward that the test methods of water-chilling unit should both adopt COP and IPLV,at the same time adopt the formulae and parameters on the effective national standards and rules.